A fuzzy MADM (Multiple Attribute Decision Making) expert system for job matching / Refnaldy Azuardi - Azuardi, Refnaldy (2005)
Registered to jobs searching websites, searching the newspaper advertisement and other method are used in job searching among students. Students faced with a lot of problems to find suitable job when they graduate soon because of no facilities especially from the faculty itself that can assist in providing alternative jobs for them. So, integration between fuzzy and Multiple Attribute Decision Making (MADM) method will become the technique to solve this problem. The main purpose of this research is to develop the Fuzzy MADM expert system prototype for job matching problem. Students from four courses have been selected in this research and matched with six jobs selected. This system can assist students in finding suitable jobs that match their skills and qualifications. Weight will assign to computer knowledge and skill and additional values sub-attributes were the earliest stage before fuzzy process started